2013
DOI: 10.5812/ijhrba.8554
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Parental Monitoring and Affiliation with Deviant Peers in Adolescents’ Sexual Risk Taking: Toward an Interactional Model

Abstract: BackgroundAdolescence is considered as an important phase for beginning sexual high risk behaviors that increases the possibility of negative, unpleasant and problematic consequences like unwanted pregnancy and probability of copulative disease transmission.ObjectivesTo determine the prevalence of sexual risk taking among students in Tehran and to develop and test a model for the relationship between parental monitoring and affiliation with deviant peers as they predict youth risky sexual behaviors.Materials a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Stattin and Kerr (Kerr & Stattin, 2000; Stattin & Kerr, 2000) defined parental monitoring as the parents’ knowledge about their child’s activities: knowing where, how, and with whom their children spend their time. Numerous studies have linked poor maternal monitoring with children RTB and externalizing behavioral problems (Ahmadi, Khodadadi Sangdeh, Aminimanesh, Mollazamani, & Khanzade, 2013; Dever et al, 2012; DiClemente et al, 2001; Huebner & Howell, 2003; Reynolds, MacPherson, Matusiewicz, Schreiber, & Lejuez, 2011). Furthermore, this source of information was found to be a substantially stronger predictor of child’s engagement in RTB and externalizing behavioral problems, than other parenting behaviors such as parental control and surveillance (Crouter, Bumpus, Davis, & McHale, 2005; DiClemente et al, 2001; Fletcher, Steinberg, & Williams-Wheeler, 2004; Kerr & Stattin, 2000; Stattin & Kerr, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Stattin and Kerr (Kerr & Stattin, 2000; Stattin & Kerr, 2000) defined parental monitoring as the parents’ knowledge about their child’s activities: knowing where, how, and with whom their children spend their time. Numerous studies have linked poor maternal monitoring with children RTB and externalizing behavioral problems (Ahmadi, Khodadadi Sangdeh, Aminimanesh, Mollazamani, & Khanzade, 2013; Dever et al, 2012; DiClemente et al, 2001; Huebner & Howell, 2003; Reynolds, MacPherson, Matusiewicz, Schreiber, & Lejuez, 2011). Furthermore, this source of information was found to be a substantially stronger predictor of child’s engagement in RTB and externalizing behavioral problems, than other parenting behaviors such as parental control and surveillance (Crouter, Bumpus, Davis, & McHale, 2005; DiClemente et al, 2001; Fletcher, Steinberg, & Williams-Wheeler, 2004; Kerr & Stattin, 2000; Stattin & Kerr, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…3 6 7 During adolescence, relational problems with parents and peers, academic failure, and various form of social maladjustment manifest as delinquent behaviors, such taking drugs, using alcohol and cigarette, and engaging in early sexual relations. 8 9 10 Therefore, adolescents in multicultural families are assumed to be at risk for substance use and sexual behavior.…”
Section: Introductionmentioning
confidence: 99%
“…The same agent can decrease the interaction of the child with the parent. Less emotional attachment to family leads to the decrease of internalization of norms and traditional practices for the adolescents, which in turn causes adolescents to socialize and develop relationships with peer groups and various unfamiliar, and abnormal social networks that tend to be drawn to high-risk and traumatic behaviors [21][22]. In relation to the status of high-risk behaviors, the study showed that single-parent adolescents possess less adjustment compared to twoparent adolescents, and therefore are more inclined to high-risk behaviors.…”
Section: Discussionmentioning
confidence: 99%